Empowerment of Health Cadres in Improving Skills through Training on Early Detection and Warning Signs of Pregnancy in Kabunan Village, Balen District, Bojonegoro Regency - Handayani, Aris; Triyawati, Lilik; Wahyuni, Sri (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Maternal Mortality Rate (MMR) in Indonesia remains high. One of the contributing factors to the high maternal mortality rate is undetected high-risk pregnancies. Antenatal Care (ANC) is crucial as it not only serves to monitor the health of the mother and fetus but also to detect potential risks during pregnancy. The objective of this community service is to enhance the knowledge and skills of health cadres in the early detection of high-risk pregnancies. The target audience for this community service activity consists of 30 Posyandu cadres from Kabunan Village within the Balen Health Center area, Bojonegoro. The methods used in this activity include the provision of materials through lectures and discussions, distribution of leaflets, and a simulation of filling out the Poedji Rochjati Score Card. The results of the activity show that there was an increase in knowledge after the training, with participants demonstrating a rise in good knowledge from 3.39% to 8.30%. The cadres' skills in performing early detection of high-risk pregnancies showed an average score of 84, and 66.7% of the participants performed very well in the health education category. Conclusion: The improvement in knowledge and skills in filling out the Poedji Rochjati Score Card for early detection and referral in preparation for complications in both mothers and newborns can contribute to reducing maternal and child mortality, particularly in Kabunan Village within the Balen Health Center's jurisdiction, Bojonegoro.